Content Analysis of Tamil TV Commercials Aimed at Women in the Post War Context - Shivany, S.; Velnampy, T. (13th International Conference on Business Management 2016, 2016)
Television advertising is an industry that has a huge investment opportunity. To help evaluate whether or not advertising investments are earning the best return on investment, it is important to know how effectively television ads capture and maintain audience attention and engage viewers. People watching televisions are bombarded with images and slogans through advertisements. There are more concerns regarding the representation of women in the media. Consumers in the Sri Lankan Post war environment are confronted with a large number of TV commercials for many products and services. In such clustered media environment, one of the major challenges for advertising is to attract and retain the attention of consumers, who have redeveloped a purchased patterns among huge number of brands. In the post war context women have much supremacy on the purchase decision making. Marketers attract the women as a special segment to reach their sales target. It is important to know the content of the TV commercials to fine-tune the best content compare with the competitors in the market. Identifying the content of the commercials form and the consumers’ perspective helps to enrich the commercials in an expected way. Content analysis method was used to analyze the content of 14 TV commercials aimed at women in the post war context. Data were collected from 30 women on their perspective on the contents in the advertisements were analyzed. Through the coding method, researchers categorized the contents of the TV commercials as physical attractiveness, beauty, uniqueness, safety, ease, being modern, and nourishment. Finding shows that most of the TV commercials aimed at women comprehended of the physical attractiveness, and the beauty, to attract the women in the post war background.
Keywords: Content Analysis; Tamil TV Commercials; Post-War Context